2016
DOI: 10.1074/jbc.m115.683763
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Disorder of the Most Immature Cu, Zn-Superoxide Dismutase Leading to Amyotrophic Lateral Sclerosis

Abstract: Misfolding of Cu,Zn-superoxide dismutase (SOD1) is a pathological change in the familial form of amyotrophic lateral sclerosis caused by mutations in the SOD1 gene. SOD1 is an enzyme that matures through the binding of copper and zinc ions and the formation of an intramolecular disulfide bond. Pathogenic mutations are proposed to retard the post-translational maturation, decrease the structural stability, and hence trigger the misfolding of SOD1 proteins. Despite this, a misfolded and potentially pathogenic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 55 publications
4
33
0
Order By: Relevance
“…Furthermore, we find strong correlations within the zinc-binding loop (residues 49–60) only in A4V–SOD1, whereas in WT-, T2D-, and T2D/A4V–SOD1 these correlated motions are suppressed (Figure S6). The zinc-binding loop has been suggested to allosterically regulate the conformation of the C4F6 epitope (Bosco et al, 2010), which is directly linked to neural-toxicity of SOD1 in a primary microglia activation assay (Furukawa et al, 2015; Rotunno et al, 2014). We propose that in A4V–SOD1 the cross-correlated motions promote the exposure of the disease-related epitope, and that the T2D/A4V double mutant prevents this effect.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we find strong correlations within the zinc-binding loop (residues 49–60) only in A4V–SOD1, whereas in WT-, T2D-, and T2D/A4V–SOD1 these correlated motions are suppressed (Figure S6). The zinc-binding loop has been suggested to allosterically regulate the conformation of the C4F6 epitope (Bosco et al, 2010), which is directly linked to neural-toxicity of SOD1 in a primary microglia activation assay (Furukawa et al, 2015; Rotunno et al, 2014). We propose that in A4V–SOD1 the cross-correlated motions promote the exposure of the disease-related epitope, and that the T2D/A4V double mutant prevents this effect.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, we have shown that reduction of the disulfide bond drastically increases fluctuation of the loops IV and VII (Fig. 8b), temporarily “peels” those loops off from the β-barrel scaffold, and thus potentially exposes the epitope of anti-SOD1 int antibody [55]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…WT SOD1 is highly expressed in motor neurons, approaching supersaturation, which could enhance its probability of misfolding [43]. In vitro, purified WT SOD1 can be readily induced to aggregate into amyloid-like fibrillary structures by de-metalation (Cu) and disulfide reduction [44][45][46][47][48][49][50][51][52][53][54]. Within the amino acid sequence of SOD1 there are several small sequence motifs that are inherently amyloidogenic [55].…”
Section: Introductionmentioning
confidence: 99%